Penguatan Kapasitas Pokdarwis untuk Pengurangan Risiko Bencana di Destinasi Pariwisata Dieng - Destha Titi Raharjana; Mohamad Yusuf; Arry Retnowati (Faculty of Cultural Sciences, 2020)
Efforts to reduce disaster risks should be a main endeavour in every development, including in tourism sector. In many places, the tourism industry is vulnerable to disasters, either directly or indirectly. Either the tourism sector triggers disasters, or it can be affected by disasters. The Dieng Plateau area is one of the leading tourism destinations in Central Java which has potentials to attract tourists. But behind its beautiful charm, this destination holds a threat. The people of Dieng Kulon, Batur District, Banjarnegara Regency, Central Java live in a disaster-prone area. They do not forget the series of disasters had occured around them. On the other hand, the surrounding nature in the village provides economic benefits, one of them comes from the tourism sector. The disaster risk reduction (DRR) approach is strategic to be applied in this village. Through the Education for Sustainability Development (ESD) program, the Dieng Pandawa Tourism Awareness Group (Pokdarwis) has to be strengthened its role so that the Pokdarwis is able to become one of the elements in DRR, especially the ability related to the process of rescueing tourists. Disaster threats on a tourism location makes the tourism industry very vulnerable, but it should be attempted that this destination or industry will become resilient at the same time. Disaster risk reduction programs and capacity building for Pokdarwis are strategic to be implemented and directed in building disaster mitigation plans.====Upaya mengurangi resiko bencana perlu menjadi arus utama dalam setiap pembangunan, termasuk di sektor kepariwisataan. Di banyak tempat, industri pariwisata rentan dengan bencana, baik secara langsung ataupun tidak langsung. Di satu pihak sektor pariwisata memicu terjadinya bencana, tetapi di pihak lain dapat menjadi yang terdampak. Kawasan Dieng Plateau salah satu destinasi pariwisata unggulan Jawa Tengah yang potensial mendatangkan wisatawan. Namun di balik pesonanya yang indah, destinasi ini menyimpan ancaman. Masyarakat Dieng Kulon, Kecamatan Batur, Kabupaten Banjarnegara Jawa Tengah tinggal di kawasan rentan bencana. Mereka tidak lupa terhadap rentetan kejadian bencana di sekitar mereka tinggal. Di sisi lain, alam sekitar di desa memberikan manfaat ekonomi, salah satunya dari sektor pariwisata. Pendekatan pengurangan resiko bencana (PRB) menjadi strategis untuk diterapkan di desa tersebut. Melalui program Education for Sustainabe Deveopment (ESD), Kelompok Sadar Wisata (Pokdarwis) Dieng Pandawa diperkuat perannya supaya mampu menjadi salah satu unsur dalam PRB, khususnya kemampuan terkait proses penyelamatan wisatawan. Adanya ancaman bencana terhadap lokasi pariwisata menjadikan industri pariwisata sangat rapuh (vulnerable), tetapi di pihak lain diharapkan secara bersamaan destinasi atau industri ini menjadi tangguh (resilient). Program pengurangan resiko bencana dan penguatan kapasitas Pokdarwis menjadi strategis untuk dijalankan dan diarahkan untuk menyusun perencanaan mitigasi bencana.